2016
DOI: 10.1007/s00383-016-3988-9
|View full text |Cite
|
Sign up to set email alerts
|

Airway foreign bodies in pediatric patients: anatomic location of foreign body affects complications and outcomes

Abstract: The in-hospital mortality rate for airway foreign bodies is 2.5 %. The anatomic location of airway FB in pediatric patients varies by age, and affects the need for mechanical ventilation and in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 15 publications
5
34
2
3
Order By: Relevance
“…The mortality rate in this group was 0.3%, lower than previously reported by Johnson et al, who found a 2.5% mortality rate using the KID for 2003 to 2012. This was reviewed for a diagnosis of an AFB using International Classification of Diseases, Ninth Revision codes, so this group would have included patients who had not undergone bronchoscopy . Foltran et al's meta‐analysis of AFBs in children reported a pooled proportion of mortality of 0.062 9 ; again, this did not include only children undergoing removal of the AFB by bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate in this group was 0.3%, lower than previously reported by Johnson et al, who found a 2.5% mortality rate using the KID for 2003 to 2012. This was reviewed for a diagnosis of an AFB using International Classification of Diseases, Ninth Revision codes, so this group would have included patients who had not undergone bronchoscopy . Foltran et al's meta‐analysis of AFBs in children reported a pooled proportion of mortality of 0.062 9 ; again, this did not include only children undergoing removal of the AFB by bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms can be absent or nonspecific. Almost 2,000 children are admitted yearly to US hospitals for this diagnosis, and the mortality rate has been reported to be up to 2.5% . Bronchoscopy is the only way to rule out an airway foreign body as chest radiographs can be normal .…”
Section: Introductionmentioning
confidence: 99%
“…[67] Other complications include neurologic disability, recurrent pneumonia, pulmonary abscess, and bronchiectasis. [8910]…”
Section: Introductionmentioning
confidence: 99%
“…[8] The National Safety Council identified the rate of fatal and nonfatal choking among American children in the general population as 0.43 and 20.4/100,000 population, respectively. [11]…”
Section: Introductionmentioning
confidence: 99%
“…Puede manifestarse con fiebre, tos crónica, hemoptisis, neumonía y atelectasias [9]. LOCALIZACIÓN Dentro de la vía aérea los síntomas van a depender de las diferentes localizaciones [1, 2, 9, 10]:…”
Section: Introductionunclassified